1997
DOI: 10.1073/pnas.94.5.2019
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic immunophilin ligands stimulate structural and functional recovery in neurodegenerative animal models

Abstract: Although immunosuppressant immunophilin ligands promote neurite outgrowth in vitro, their neurotrophic activities are clearly independent of their immunosuppressive activity. In the present report, a novel nonimmunosuppressive immunophilin ligand, GPI-1046 (3-(3-pyridyl)-1-propyl (2S)-1-(3,3-dimethyl-1,2-dioxopentyl)-2-pyrrolidinecarboxylate) is described. In vitro, GPI-1046 bound to FK506 binding protein-12 and elicited neurite outgrowth from sensory neuronal cultures with picomolar potency with maximal effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
198
4
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(208 citation statements)
references
References 31 publications
4
198
4
2
Order By: Relevance
“…Several studies report that FK506 and related non-immunosuppressive immunophilin ligands, such as GPI-1046 and V10367, have neurotrophic/ neuroprotective effects on dopaminergic neurons following MPTPor 6-OHDA-induced lesion (Steiner et al, 1997;Costantini et al, 1998Costantini et al, , 2001Ross et al, 2001;Zhang et al, 2001a;Tanaka et al, 2002a). Neurotrophic effects to dopaminergic neurons are also observed in vitro (Costantini and Isacson, 2000;Guo et al, 2001).…”
Section: Immunophilin Ligandsmentioning
confidence: 84%
See 1 more Smart Citation
“…Several studies report that FK506 and related non-immunosuppressive immunophilin ligands, such as GPI-1046 and V10367, have neurotrophic/ neuroprotective effects on dopaminergic neurons following MPTPor 6-OHDA-induced lesion (Steiner et al, 1997;Costantini et al, 1998Costantini et al, , 2001Ross et al, 2001;Zhang et al, 2001a;Tanaka et al, 2002a). Neurotrophic effects to dopaminergic neurons are also observed in vitro (Costantini and Isacson, 2000;Guo et al, 2001).…”
Section: Immunophilin Ligandsmentioning
confidence: 84%
“…Nevertheless, current clinically available immunophilin ligands, including FK506 and cyclosporine A, are immunosuppressive, which limits their chronic use. However, neither calcineurin inhibition nor binding to FKBP-12 were found to be necessary for the neurotrophic effects of immunophilin ligands (Steiner et al, 1997;Costantini et al, 2001;Guo et al, 2001;Klettner et al, 2001;Zhang et al, 2001a;Tanaka et al, 2002b). This fact, together with the neuroprotective effects of immunophilin ligands in models of neurodegenerative disorders (reviewed by Pong and Zaleska, 2003), has led to the design of small ligands that bind to immunophilins, but are not immunosuppressive since they do not interact with calcineurin (e.g.…”
Section: Immunophilin Ligandsmentioning
confidence: 99%
“…Interestingly, such effectiveness was recognized with both early and late administration (7 to 28 days after injury) (Steiner et al, 1997b;Zhang et al, 2001). The present study observed a striking colocalization of CyCAP and cyclophilin C mRNAs in the activated macrophages of the ischemic core.…”
Section: Discussionmentioning
confidence: 99%
“…studies of GPI used in other nerve lesion paradigms have shown that, following oral administration of the compound, increased doses, nearly twice the intraperitoneal or subcutaneous dose are necessary to provide efficacy [13]. Thus, we utilized GPI at a dose of 30 mg/kg to assess the oral efficacy of the compound.…”
Section: Oral Treatment With Gpi Maintains Erectile Function-previousmentioning
confidence: 99%